Possible directions in the protection of the neglected invertebrate biodiversity. (30th July 2013) - D'Amen, M.; Bombi, P.; Campanaro, A.; Zapponi, L.; Bologna, M. A.; Mason, F.
<x xml:space="preserve">Abstract</x> Read the Feature Paper: Protected areas and insect conservation: questioning the effectiveness of Natura 2000 network for saproxylic beetles in Italy Commentaries on this Feature Paper: Institutional vertebratism hampers insect conservation generally; not just saproxylic beetle conservation; Knowledge gaps in protected area effectiveness